Modified cassava flour (MOCAF) content of cassava (Manihot esculenta CRANTZ) in North Sumatera. (May 2019) - Kardhinata, E H; Purba, E; Suryanto, D; Rusmarilin, H
Abstract: Research on Modified Cassava Flour (MOCAF) content in three cassava genotypes has been carried out at Laboratorium Sekolah Tinggi Penyuluh Pertanian, Jl. Binjai Km 10 Medan in November 2014. The research objective was to determine the MOCAF yield produced based on cassava genotypes in North Sumatra. Two genotypes and one variety of cassava were used as samples, Adira-1 (V1) variety, Malaysia (V2) and Merah/Gondoruwo (V3) genotypes. Fermentation using BIMO-CF starter with 24 hours soaking time. The results showed that MOCAF yield of three genotypes/varieties ranged from 33-38%. The highest yield was found in Malaysia genotype, followed by Merah/Gondoruwo and Adira-1, respectively 38%, 35% and 33%.